CERITA RAKYAT TIMUN EMAS: GAMBARAN RUNTUHNYA IDEOLOGI PATRIARKAL - Reno Wulan Sari (Jurnal Gramatika, 2015)
Patriarchal ideology puts women as subordinate and feel inferior in various facets of life. thought it was getting counter-discourse presented by the text tale of Timun Emas. In the text, described the loss of the role of men as the highest authority in live. The role of men is represented by four figures; the husband, Ki Butakala, Ki Pertapa, and the Prince. They have superiority , but then lost control of the two rival  of women; Nyi Niken and Timun Emas. In the text implied that Nyi Niken and Timun Emas does not need a male figure in their lives. In accordance with the above description, analysis tale of Timun Emas uses feminist approach to look at the differences in the function and  role of the human (between of man and woman). So it can be concluded that the tale of Timun Emas events that indicate a loss of patriarchal ideology